Ironie in die Johaimesevangelie - Kotzé, P. P. A. (Hervormde teologiese studies, 1987)
Irony in the Gospel of John An exponent of literary theory and criticism described the shift of focus from the text to the reader as a revolution. One of the main features of irony is the intensive involvement of the reader. As far as John is concerned, some scholars are convinced that 'In the Fourth Gospel theology is irony'. This may be an exaggeration, but emphasises the need to ascertain to v/hat extent irony is used in John and what contribution the study of irony in John can make to the better understanding of the message of the Gospel. In order to answer these questions, one must first determine what irony is, how it functions and how it can be detected in a text. This article is an attempt in this direction.